Sustainable Branding for Local Products: Empowering Rural Economic Development - Nur Maghfirah Aesthetika; Poppy Febriana; Ilmi Usrotin Choiriyah; Romadhona Safitri; Nabila Ayu Bakta (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article presents a program designed to foster sustainable economic independence within Kemlagi Village, Indonesia, by harnessing the potential of small businesses. The program aims to motivate and engage the local community through effective communication schemes and empowerment initiatives, maximizing the village's resources and potential. By focusing on the branding of local honey products, the program enhances the value and marketability of these products while promoting the understanding of the significance of branding among the villagers. The training method involves short sessions covering branding strategies and media utilization, followed by interactive Q&A and discussions. The results highlight increased knowledge and skills in branding, paving the way for the village to transform into a sought-after Honey Tourism Village. The implications of this study shed light on how local communities can achieve economic sustainability through targeted empowerment programs and brand development. Highlights: Engaging Rural Communities: The program aims to motivate and involve local residents directly in maximizing their village's potential by harnessing the power of branding for local products. Enhancing Marketability: Through targeted training sessions, the program seeks to equip villagers with the knowledge and skills needed to elevate the value and market appeal of their local honey products. Towards Sustainable Development: By transforming Kemlagi Village into a Honey Tourism Village, the program sets the stage for long-term economic sustainability, leveraging the natural resources and unique offerings of the community. Keywords: Rural Economic Sustainability, Branding, Local Products, Empowerment, Honey Tourism Village